Etika Siber dan Formasi Iman di Ruang Digital: Integrasi Pemikiran Charles Ess dalam Pendidikan Agama Kristen Berbasis Daring - Santoso, Desy Irawaty; Wiryadinata, Halim (EPIGRAPHE (Jurnal Teologi dan Pelayanan Kristiani), 2025)
This study aims to explore Charles Ess’s theoretical framework regarding how discourse shapes ethics in the digital sphere. The acceleration of digitalization has altered human attitudes and behaviors, producing a modern identity that transcends conventional boundaries within the Internet of Things. The increasing detachment of these behavioral shifts from moral and ethical foundations calls for meaningful dialogue in Christian religious education. The core argument of this research is that Ess’s concepts offer a valuable ethical and spiritual discourse for guiding behavior in digital contexts. By employing a literature-based method as a secondary data source, this study constructs a logical framework to support its claims. The findings suggest a dialogical encounter between Charles Ess’s ideas and Christian spiritual values within religious education, which contributes to the construction of an ethical approach to digitalization. In conclusion, this dialogical space enables Christian values to catalyze the emergence of ethical norms within the educational framework.   Abstrak Tujuan dari penelitian ini yaitu menjelaskan konsep pemikiran Charles Ess sebagai diskursus pembangunan etika di ruang digital. Perkembangan dan pertumbuhan digitalisasi mengubah sikap dan perilaku manusia menuju manusia modern tanpa memiliki batas di ruang internet of things. Pergeseran perilaku manusia tidak memiliki batas dan nilai, sehingga mengundang pendidikan agama Kristen untuk berdialog. Argumentasi studi ini yaitu konsep Charles Ess memberikan discourse etika dan nilai spiritual dalam membentuk sikap dan perilaku pengguna Internet of Things. Untuk menjawab dan mendukung argumentasi tersebut, maka penelitian ini menggunakan metode kepustakaan sebagai sumber sekunder dalam membangun logika berpikir. Hasil dari studi ini menunjukkan adanya hubungan antara pemikiran Charles Ess dan nilai spiritual Kristiani dalam pendidikan agama Kristen untuk menciptakan etika dalam dunia digital. Kesimpulannya, ruang dialog memberikan tempat bagi nilai Kristiani untuk menjadi pemicu terciptanya etika dalam bingkai pendidikan.